Case report: A case of complete clinical response in a patient experiencing high microsatellite instability unresectable colon cancer being treated with a PD-L1 inhibitor after interstitial pneumonia - Wang, Luo; Mou, Haibo; Hou, Xuehua; Liao, Qin (Frontiers in Oncology, 2023)
Immune checkpoint inhibitors (ICI) have dramatically transformed the treatment landscape for metastatic colorectal cancer (mCRC) with deficient DNA mismatch repair (dMMR) or high microsatellite instability (MSI-H). Envafolimab, a novel programmed death-1 ligand 1 (PD-L1) inhibitor, has been reported to be efficient and safe for the management of advanced MSI-H/dMMR solid tumors. Here, we report the case of a 35-year-old female patient with MSI-H/dMMR mCRC who was treated with envafolimab following mFOLFOX6 (oxaliplatin, leucovorin, and fluorouracil) plus bevacizumab. While suffering from interstitial pneumonia after chemotherapy, the patient achieved a complete clinical response with the use of envafolimab without additional adverse events. Thus, PD-L1 inhibitors may be potential candidates for treating patients with MSI-H/dMMR mCRC.